2022
DOI: 10.3390/ijerph19041996
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Self-Esteem with the Level of Independent Functioning and the Primary Demographic Factors in Persons over 60 Years of Age

Abstract: Self-esteem reflects the way we see ourselves. The aim of this study was to determine the relationship among self-esteem, bio-psycho-social functioning, and sociodemographic conditions in the elderly. The study included 300 individuals over 60 years of age living in their home environment. The employed research tools included the Abbreviated Mental Test Score, Rosenberg Self-Esteem Scale (RSES), and EASYCare Standard 2010 questionnaire involving the following scales: independence score, risk of breakdown in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Actually, prior researchers have described that providing support for people to engage in social interaction is a form of depression prevention [48]. Other scholars further demonstrated that limited communication leads stroke survivors to experience a reduced selfesteem [49], and limited activities could cause QOL reductions among stroke patients [50,51]. Together, the findings of this study and past research suggest that it could be necessary to consider approaches to improving the motor and interaction functions of stroke survivors as of 12 months after discharge.…”
Section: Discussionmentioning
confidence: 55%
“…Actually, prior researchers have described that providing support for people to engage in social interaction is a form of depression prevention [48]. Other scholars further demonstrated that limited communication leads stroke survivors to experience a reduced selfesteem [49], and limited activities could cause QOL reductions among stroke patients [50,51]. Together, the findings of this study and past research suggest that it could be necessary to consider approaches to improving the motor and interaction functions of stroke survivors as of 12 months after discharge.…”
Section: Discussionmentioning
confidence: 55%
“…Currently, the study attempts to assess the effect of regular physical activity on the level of GSE and life satisfaction in different age groups and populations [ 26 ]. Many previous studies have shown that an increase in physical activity has a positive effect on self-esteem, while a sedentary lifestyle is associated with a decrease in physical activity [ 27 , 28 , 29 , 30 ]. A study by Masana et al [ 31 ] has shown that older people with low self-esteem or anxiety disorders are considerably more likely to lead an unhealthy lifestyle, which is characterized by low levels of physical activity or the use of stimulants such as smoking.…”
Section: Discussionmentioning
confidence: 99%
“…When a diet was introduced, the level of global self-assessment changed from medium to high. The obtained results suggest that the key role in the change in GSE may be played by the change in body weight and the level of adipose tissue associated with the change in figure [ 30 ]. Body image and self-esteem have already been empirically linked; however, the relationship between them in older people requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…The collection of potential end-users' opinions about older persons' robot-related needs and requirements was part of the project. We previously presented the findings of quantitative experiments that used the Users' Needs, Requirements, and Abilities Questionnaire (UNRAQ)-a mixedmethodology tool developed as a component of the research project [82][83][84][85][86][87][88][89][90][91][92][93][94].…”
Section: Methodsmentioning
confidence: 99%